FROM ABC TO ENGLISH: STRATEGIES TO BOOST CHILDREN'S SPEAKING CONFIDENCE EARLY - Ririn Yusrini Mudawamah; Ela Latifah; Syifa Nurhikmah Lestari; Selnistia Hildayani (Jurnal Intelek Insan Cendikia, 2025)
Speaking is one of the key skills in learning English, especially for young children who are at an optimal stage of language development. This article discusses effective strategies in building children's confidence in speaking English from the basic introduction stage, from the alphabet (ABC) to the ability to speak fluently. Some of the approaches discussed include the use of songs and games, storytelling, role play, as well as the application of Total Physical Response (TPR) and Communicative Language Teaching (CLT) methods. The article also integrates theories from experts such as Krashen, Vygotsky, Bruner and Asher as the theoretical foundation. The results show that a positive learning environment, support from teachers and parents, and fun learning activities can significantly increase children's courage to speak English. With the right approach, children are not only able to recognize basic vocabulary, but can also grow into confident communicators.